SURFACE MODIFICATION OF RUBBER FROM END-OF-LIFE TIRES FOR USE IN CONCRETE: A DESIGN OF EXPERIMENTS APPROACH - Bruno F. Urbano; Victor Campos-Requena; Mauricio Pradena; Eduardo García; Paulo Flores; Bárbara Villa; Carlos Medina (Journal of the Chilean Chemical Society, 2020)
A large amount of discarded tire waste generated year after year has encouraged the scientific community to seek alternatives for recycling or reusing this waste. The cross-linked nature and the high number of additives in tires make recycling significantly difficult. Thus, the use of particulate rubber as filler for other materials such as concrete has emerged as an attractive alternative. However, the hydrophobic nature of the rubber and hydrophilic particles of cement decreases the compatibility at the cementitious matrix-rubber interface, affecting the concrete's final performance. This work presents a method based on hydrogen peroxide and Fenton for the oxidation of rubber particles from end-of-life tires to introduce hydrophilic groups on the surface of the particles to improve compatibility at the interface. The method was studied from an experimental design approach using a Rechtschaffner Resolution V design, PCA and PLSR in order to evaluate variables such as time, temperature and reactants. The concentration of H2O2 and reaction temperature was shown to increase the oxidation, while Fenton reduces the time of oxidation.